Adherence therapy following acute exacerbation of schizophrenia: A randomised controlled trial in Thailand. (February 2015) - von Bormann, Suparpit; Robson, Deborah; Gray, Richard
Background: Up to 50% of patients with schizophrenia are non-adherent with antipsychotic medication. Aims: To establish the efficacy of adherence therapy (AT) compared to treatment as usual (TAU) in improving clinical outcomes in patients with schizophrenia following an acute exacerbation of illness. Method: A parallel-group, single-blind, randomised controlled trial. Fieldwork was conducted in Thailand. Patients received eight weekly sessions of AT in addition to TAU. The primary outcome was improvement in psychopathology (measured using the Positive and Negative Syndrome Scale (PANSS)) at 26-week follow-up. Secondary outcomes included patient attitudes towards medication, global functioning and side-effects. Results: In total, 70 inpatients with schizophrenia were recruited to the trial. At 26-week follow-up, PANSS total scores improved in the AT compared to the TAU group by a mean of −3.94 points (effect size = 0.24). The number needed to treat (NNT) was 5. There was no significant effect on patients' attitudes towards treatment, functioning or medication side-effects. No treatment-related adverse effects were reported. Conclusion: AT improves psychopathology in Asian patients with schizophrenia following an acute exacerbation of illness.